LEGAL MODEL OF STATE COERCION AS TO A SPECIAL CATEGORY OF PERSONS - T. M. Sekretareva (Russian Journal of Economics and Law)
Objective: to develop a legal model of state coercion against individuals with mental disorders.Methods: dialectical method, analysis, synthesis, description, explanation.Results: identifying features of the semantic and meaningful understanding of state coercion against persons with mental disorders allowed to designate state coercion in respect of special category of persons as an independent state coercion, which has an interdisciplinary and multidis- ciplinary character.Scientific novelty: for the first time the article investigated the place and role of state coercion in relation to special categories of persons in the system of legal policy means; state coercion against a particular category of persons is considered as an independent form of state coercion. The classification of actors is proposed, who are involved in the application of state coercion against persons with mental disorders, as well as the structure of state coercion, consisting of preventive measures; suppressive measures; measures to ensure proceedings in criminal, civil cases, cases of administrative offenses; punishment; other enforcement measures.Practical significance: the research results can be used to improve the system of state coercion in the Russian Federation.